Shipbuilding tendencies in the context of digitalization - Ieva Verseckaitė; Artūras Jakubavičius (Mokslas: Lietuvos Ateitis, 2024)
Over the last few years, the new industrial revolution 4.0 has spread across industries and affected the shipbuilding industry as well. Shipbuilding based on the principles of Industry 4.0 would transform the design, production, operation, maintenance, communication and value chains of the shipbuilding industry in all aspects. In order to create new value, the ship must become smart and must be manufactured in a smart shipbuilding process. Shipbuilding as an assembly industry is reliant on international trade because a large part of the value of a ship depends on intermediate inputs that are sourced from various countries around the world. Rapidly developing technologies also bring economic changes – more technologically advanced companies could be more efficient and would occupy a larger market share in the future. In the first part of this article systematics of value chains in the shipbuilding sector is analysed the added value created by digital technologies is evaluated in the efficient value creation chain, in the second part research methods are presented – correlation-regression analysis and the SAW method, in the third part the development trends of shipbuilding are evaluated.